LUNG CANCER LIFETIME RISKS IN COHORT STUDIES OF URANIUM MINERS. Issue 2 (31st October 2020) - Tomasek, Ladislav
Abstract: The article summarizes the most recent results from the cohorts of uranium miners, particularly the risks at low exposures and the risk models with modifying effects of exposure rate, age and time since exposure, which are used for the calculation of lifetime risks (LRs). The excess relative risks per unit exposure (ERR/WLM) arising from low exposures were found up to 10 times higher than the crude risk coefficients. For studies that reported models with modifying effect of age, time since exposure and exposure rate, LRs were calculated using the BEIR VI projection. These LRs were also calculated for a model with effect modification on the annual exposure rate. The results were prepared for the UNSCEAR report on 'Lung cancer from exposure to radon.' (1 )